2018
DOI: 10.3389/fnbeh.2018.00141
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the Innate Immune System in Susceptibility and Resilience After Social Defeat Stress

Abstract: Dysregulation of innate immune responses has frequently been reported in stress-associated psychiatric disorders such as major depression. In mice, enhanced circulating cytokine levels as well as altered innate immune cell numbers have been found after stress exposure. In addition, stress-induced recruitment of peripheral monocytes to the brain has been shown to promote anxiety-like behavior. However, it is yet unclear whether specific differences in the innate immune system are associated with stress suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 69 publications
4
42
0
Order By: Relevance
“…This adaptive reaction leads to a stress response in the subordinate individual (Abbott et al, 2003), with elevations in the stress hormone cortisol as the hypothalamic-pituitary-adrenal axis (HPA) is activated, and this stress response may be modulated by the social environment, in particular with isolation from others (Ruis et al, 2001;Ruis et al, 1999). Social defeat effects may also impact additional physiological processes, such as reduction in the neurotransmitter dopamine's transporter (DAT) binding (Isovich et al, 2001) and the dysregulation of innate immune responses (Ambrée et al, 2018). When the defeating situation persists and there is no means of escape, the animal feels trapped (entrapment) and the stress response may become chronic, known as arrested flight (i.e., the flight instinct of the autonomic nervous system is suppressed, Dixon et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…This adaptive reaction leads to a stress response in the subordinate individual (Abbott et al, 2003), with elevations in the stress hormone cortisol as the hypothalamic-pituitary-adrenal axis (HPA) is activated, and this stress response may be modulated by the social environment, in particular with isolation from others (Ruis et al, 2001;Ruis et al, 1999). Social defeat effects may also impact additional physiological processes, such as reduction in the neurotransmitter dopamine's transporter (DAT) binding (Isovich et al, 2001) and the dysregulation of innate immune responses (Ambrée et al, 2018). When the defeating situation persists and there is no means of escape, the animal feels trapped (entrapment) and the stress response may become chronic, known as arrested flight (i.e., the flight instinct of the autonomic nervous system is suppressed, Dixon et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Specific to TNF-α, breast cancer patients reporting increased social satisfaction or social activities had stronger TNF-α responses to an endotoxin challenge (Marucha et al, 2005). In mice, exposure to chronic defeat can lead to alterations to the profile of immune cells present in the spleen, as well as changes in gene expression of those cells, resulting in increased production of TNF-α (Ambrée et al, 2018). Therefore, the immune system can respond to social interactions and affect changes in inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study has found that voluntary exercise increases resilience to CSDS in mice (Mul et al, ), which indicates that voluntary exercise may be an effective and useful intervention to increase resilience to social defeat stress in humans. Gut microbiota, diet, and the immune system have also been implicated in resilience to CSDS in mice (Ambree, Ruland, Scheu, Arolt, & Alferink, ; Aubry et al, ; Kingston et al, ; McKim et al, ; Nie et al, ; Szyszkowicz, Wong, Anisman, Merali, & Audet, ). Improvement in eating habits may help change the immune system through alterations of microbiota, which may in turn increase resilience to social defeat stress in humans, especially given the strong correlations between the immune system and resilience to CSDS (Ambree et al, ; Aubry et al, ; McKim et al, ; Nie et al, ; Szyszkowicz et al, ).…”
Section: Social Status and Mtdmentioning
confidence: 99%
“…Gut microbiota, diet, and the immune system have also been implicated in resilience to CSDS in mice (Ambree, Ruland, Scheu, Arolt, & Alferink, ; Aubry et al, ; Kingston et al, ; McKim et al, ; Nie et al, ; Szyszkowicz, Wong, Anisman, Merali, & Audet, ). Improvement in eating habits may help change the immune system through alterations of microbiota, which may in turn increase resilience to social defeat stress in humans, especially given the strong correlations between the immune system and resilience to CSDS (Ambree et al, ; Aubry et al, ; McKim et al, ; Nie et al, ; Szyszkowicz et al, ). tDCS is a noninvasive intervention that has already been applied for the treatment of depression in clinical practice (Fregni et al, ; Nitsche, Boggio, Fregni, & Pascual‐Leone, ).…”
Section: Social Status and Mtdmentioning
confidence: 99%